2018
DOI: 10.1186/s12943-018-0858-1
|View full text |Cite
|
Sign up to set email alerts
|

Tumor microenvironment participates in metastasis of pancreatic cancer

Abstract: Pancreatic cancer is a deadly disease with high mortality due to difficulties in its early diagnosis and metastasis. The tumor microenvironment induced by interactions between pancreatic epithelial/cancer cells and stromal cells is critical for pancreatic cancer progression and has been implicated in the failure of chemotherapy, radiation therapy and immunotherapy. Microenvironment formation requires interactions between pancreatic cancer cells and stromal cells. Components of the pancreatic cancer microenviro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
363
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 446 publications
(371 citation statements)
references
References 170 publications
5
363
0
3
Order By: Relevance
“…[70][71][72] Cancer cells tend to upregulate the activity of co-inhibitory signaling pathways to escape immune surveillance. 73,74 Immune checkpoint inhibitors (ICIs) alleviate immune tolerance to tumor antigens and reinvigorate the antitumor response. Anti-PD-1/PD-L1 and anti-CTLA-4 have been successfully applied in multiple cancers.…”
Section: Immune Checkpoint Inhibitormentioning
confidence: 99%
“…[70][71][72] Cancer cells tend to upregulate the activity of co-inhibitory signaling pathways to escape immune surveillance. 73,74 Immune checkpoint inhibitors (ICIs) alleviate immune tolerance to tumor antigens and reinvigorate the antitumor response. Anti-PD-1/PD-L1 and anti-CTLA-4 have been successfully applied in multiple cancers.…”
Section: Immune Checkpoint Inhibitormentioning
confidence: 99%
“…Accumulating evidences suggest that molecular components of the TME modulate cancer progression (Incio et al, 2016;Ren et al, 2018). CAFs, a key component of the TME, play major roles in supporting cancer progression (Gascard & Tlsty, 2016;Karagiannis et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that CD4 + T cells, CD8 + T cells and macrophages played important roles in the TME and tumor prognosis. In pancreatic tumor tissues, the higher proportions of CD4 + and CD8 + T cells, the better long-term prognosis for patients [40]. In breast carcinoma, annexin1 promoted polarization of M1 macrophages and induced pro-inflammatory genes [41].…”
Section: Kinase Targets Of Hub Genesmentioning
confidence: 99%